METODE PEMBELAJARAN PARTISIPATIF UNTUK PENYELENGGARAAN PROGRAM PENDIDIKAN NON FORMAL DALAM MASYARAKAT - Ibnu Syamsi (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Target of this article is to extend firmanent and user knowledge in term of non formal education, and how study participative methode used to support non formal education programs, several things whichought to become most attention in use of study participative methode for non formal education is a group study methode. The methode and technique study.There are 10 step of model for participative training, the consideration for using participative methode. In study participative there are tripartite pursuant to activity which generating of, in term on how the strategy that teachers give to student. There are two part of study participative, and study participative which concentrated on studying.